SKRIPSI EVALUASI PERSEDIAAN KOMPUTER PADA CV.CAHAYA RESKY DI SANGATTA - Elfreda Aplonia Lau, Marlina Anitasya Herman, ,LCA Robin Jonathan (EKONOMIA, 2016)
The purpose of this study was to determine the amount of needs and analyze the need for computer inventory in a year, how many times bookings must be made. Based on the background described above, then that becomes a problem in this study